Tolyprolinol, a new dipeptide from Tolypocladium sp. FKI-7981. (July 2018) - Fukasawa, Wataru; Mori, Natsuki; Iwatsuki, Masato; Hokari, Rei; Ishiyama, Aki; Nakajima, Moe; Ouchi, Takahito; Nonaka, Kenichi; Kojima, Hiroki; Matsuo, Hirotaka; Ōmura, Satoshi; Shiomi, Kazuro
Abstract A new dipeptide, named tolyprolinol, was isolated from the static culture of a fungus, Tolypocladium sp. FKI-7981. The structure of tolyprolinol was elucidated asN- acetyl-l -phenylalanyl-l -prolinol. It showed moderate antimalarial activity but did not show cytotoxicity or any other antimicrobial property.